Gender Inequality Implications in Disaster Management: A Literature Review - Yakubu, Simnom Nissi (Corpus Intellectual, 2023)
Individuals of various genders and age groups, as well as differing socio-economic backgrounds, possess unique susceptibilities that influence their encounters with disasters and their subsequent capacity for recovery. Disasters, whether natural or humaninduced, have a disproportionate impact on women and children compared to men due to pre-existing gender disparities in society. This impact is often exacerbated by poverty, social exclusion, and cultural norms that limit women's access to resources and decision-making power. This paper undertook comprehensive literature research to understand the diverse gender-related issues in disasters and the implications that gender inequality has in disaster management. The study found that even though there have been grave effects of disasters on men, there is a higher percentage of women and children who experience the grave effects of disasters. This paper thus suggests that in the bid to reduce the effects that disaster on women and children it is imperative to ensure that women are included in the formation of disaster-related policies and that the rights of women and children are acknowledged in disaster cases.